Analysis of the effects of Instrumental Chiropractic Therapy in posture and on the strength of extensors of trunk (Research, Society and Development, 2021)
Aim: Evaluate the effects of Chiropractic Instrumental Therapy on posture and shape of trunk extensor muscles. Methods: Is a study of the type of quasi-experimental cross-section, with a sample of 31 individuals. A history, then the digital photogrammetry and lumbar hand, both carried out before and after treatment with Instrumental Chiropractic Therapy. For analysis of the variables, the Wilcoxon test was applied. The conclusions were based on a 95% confidence interval and p